Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd006318.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance agonist treatments for opiate dependent pregnant women

Abstract: We didn't find any significant difference between the drugs compared both for mother and for child outcomes; the trials retrieved were too few and the sample size too small to make firm conclusion about the superiority of one treatment over another. There is an urgent need of big randomized controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(41 citation statements)
references
References 36 publications
2
37
0
2
Order By: Relevance
“…Variables influencing fetal growth and gestational age at delivery include smoking, multiple drug use and low socioeconomic status: all factors being prevalent in SMM in the present and previous studies (Cleary et al;, Fischer & Kopf, 2007, Simpson, 1957. While heroin has been associated with retarded fetal growth (Bada et al 2002, Minnes et al;2011, Minozzi et al;2008), the use of methadone has been shown to be associated with higher birth weights when compared to women who continued to use heroin. It has further been shown to HELP prevent premature labour so that fetuses exposed to methadone had a higher birth weight and less morbidity than heroin exposed babies (Finnegan et al;2010).…”
Section: Discussionsupporting
confidence: 50%
“…Variables influencing fetal growth and gestational age at delivery include smoking, multiple drug use and low socioeconomic status: all factors being prevalent in SMM in the present and previous studies (Cleary et al;, Fischer & Kopf, 2007, Simpson, 1957. While heroin has been associated with retarded fetal growth (Bada et al 2002, Minnes et al;2011, Minozzi et al;2008), the use of methadone has been shown to be associated with higher birth weights when compared to women who continued to use heroin. It has further been shown to HELP prevent premature labour so that fetuses exposed to methadone had a higher birth weight and less morbidity than heroin exposed babies (Finnegan et al;2010).…”
Section: Discussionsupporting
confidence: 50%
“…49 A recent meta-analysis did not favor one over the other. 50 No relationship has been found between maternal opioid dose and NAS. 51 Neither methadone nor buprenorphine were approved for use in pregnancy.…”
Section: Growing Epidemiologymentioning
confidence: 99%
“…This preference largely stems from longer experience with this medication. Several studies have shown improved retention in care with methadone compared to buprenorphine, both in the general population (though this effect may not be seen with fixed high doses of buprenorphine) [18] and specifically within the pregnant population [19]. Despite these distinctions, buprenorphine offers several advantages over methadone, which can be broadly categorized into those based on the medication's intrinsic properties and those based on its delivery system.…”
Section: Buprenorphine Versus Methadone (And Naltrexone) In Pregnancymentioning
confidence: 99%